Historic Ottoman Poet Biographers (Prilozi za orijentalnu filologiju, 2021)
Ottoman poet biographies, whose main purpose is to provide information about the lives, arts and works of poets, are among the most important sources of classical Turkish literature with their examples written more than once in every century from the 16th century to the XX century. The poets, whose biographies give information about their lives, are composed of people who have undertaken different duties belonging to different layers of the Ottoman social structure. After all, the most important point that brings together the biographies of these people, who have serious differences in status, is that they are poets. For the biographies of poets belonging to different strata, the tadhkirah definitely refers to the sources. These sources can be the poet himself, a close friend, another poet’s biographies or a history book, or the author himself. Historical poems written by poets on various occasions over the centuries are also one  of the written sources used by tadhkirahs. An important part of the poets in the biographies, using this systematic called abjad calculation and created by assigning numerical values to Arabic letters, they make history on the success of the sultans, the conquests of cities, an important natural event, and even the death of a book they have finished. However, besides the poets, it is seen that the authors of tadhkirahs also write down history with an approach that puts the poets in the center. These dates, which were dropped, give them the identity of a pastor, in the words of the tadhkirahs. It is not because they wrote a history book that is meant by their identity as a pastor; it is the poets’ reduction of dates on some important issues in their lives, which are based on the abjad calculation and written in verse. Within the tradition of Ottoman tadhkirah writing, many tadhkirah writers have dropped dates about the poets they mentioned in their works. In this study, information has been given from the authors of tadhkirahs, who have included history poems in their biographies, and in what ways these dates have contributed to the science of history and literature.